STRATEGI PEMBELAJARAN GURU AKIDAH AKHLAK DALAM PEMBINAAN AKHLAK MULIA PESERTA DIDIK - Nursiah; Amir Hamzah; Syamsir (Jurnal Al-Ilmi: Jurnal Riset Pendidikan Islam, 2022)
This study aims to describe the learning strategies of teachers of aqidah morals in fostering the noble character of students, knowing the supporting and inhibiting factors of the moral aqidah teacher in fostering the noble character of students, knowing the results of the implementation of the learning strategy of the teacher of moral aqidah in fostering the noble character of students. This research is included in the type of fermenology research using a qualitative research approach. The subjects in this study were the head of the madrasa, the teacher of the moral creed and the students and the object of this research was the learning strategy of the teacher of the moral creed in fostering the noble character of the students. Data collection techniques used in this study were interviews, observation and documentation, while the data analysis went through three stages, namely data reduction, data presentation, and data verification. The results of this study indicate that the learning strategies of the aqidah moral teacher in fostering the noble character of students include expository, inquiry and cooperative learning strategies. The learning strategy is combined with various learning methods so that it can improve the noble character of students. The supporting factors are the prayer room, the academic qualifications of the educator or teacher, the inhibiting factors for implementing the learning strategies of the Akhlaq teacher in fostering the noble character of students include the lack of awareness of students about the importance of education due to the low educational background of parents. In addition, the development of technology and information is also one of the inhibiting factors in fostering the noble character of students because they spend more time playing gadgets via cellphones than carrying out tasks given by teachers at school.